Empirical investigation on the impact of microcredit on women empowerment in urban Peninsular Malaysia - Abdullah Al- Mamun; Sazali Abdul Wahab; Mohammad Nurul Huda Mazumder; Zhan, S.
The main goal of this study was to assess the impact of participation in Amanah Ikhtiar Malaysia’s (AIM) microcredit program on the empowerment among urban low-income women in Peninsular Malaysia. To attain the above mentioned objective, this study utilized a cross-sectional design using stratified random sampling method to examine whether or not participation in AIM’s microcredit program improved urban low-income clients’ role in household decision making, helped the clients achieve economic security, gain more control over resources and family decisions, improve their ability to go outside to work and improve their level of legal awareness. Findings of this study revealed that participation in AIM’s microcredit program generated a positive and significant impact on women’s empowerment in Urban Peninsular Malaysia. The results suggest that AIM should, therefore, focus on increasing the outreach by targeting urban low-income women. The policy makers should focus on establishing a supportive regulatory environment to promote sustainable development of all microcredit organizations in urban Malaysia.